Evaluation of COVID-19 preventive practices among sellers in the Beni Mellal region of Morocco - Barguigua, Abouddihaj; Zahir, Ilham (The Journal of Infection in Developing Countries, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) is caused by the SARS-CoV-2 virus. It has impacted millions of individuals and caused numerous casualties. Consequently, there was a race to develop vaccines against the virus. However, there has been unequal vaccine distribution among nations, and concerns over side effects have resulted in vaccine hesitancy, reducing vaccination rates in many countries and hindering pandemic eradication. Preventive measures like well-fitted masks, frequent hand washing, alcohol-based sanitizers, and maintaining physical distance remain crucial to curb SARS-CoV-2 transmission. This study examined the adoption of these preventive measures among sellers in the Beni Mellal region of Morocco. Results: We analyzed a cohort of 700 merchants, including 40.28% middle-aged males. Among them, 53% (371/700) wore masks, with 61.08% using medical masks, and 44.05% correctly positioned their masks. Additionally, 20.29% (142/700) carried disinfectants, of whom 117 used them at least once in 30 minutes. However, physical distancing was lacking in 78.29% of sellers, particularly among young and middle-aged males (18% and 31.86%, respectively). More than 80% of the vendors had frequent physical contact with others, primarily through hands. Surprisingly, only 1% (7/700) of participants combined the following preventive measures: using a disinfectant at least once, wearing a well-fitted mask, practicing physical distancing, and avoiding contact with others. Two individuals (0.29%) refrained from touching any surfaces. Money accounted for 76.57% of commonly touched surfaces; yet only 0.29% adhered to the preventive measures while handling money. Furthermore, a majority of individuals (92.14%, 645/700) were observed touching their faces at least once.